Relationship Between Lifestyle, Stress, and Hypertension Among Productive-Age Adults - Lestari, Oktin Widia; Distinarista, Hernandia; Rahayu, Tutik (Health Access Journal, 2026)
Hypertension is a non-communicable disease whose prevalence continues to increase, including among the productive age group, and poses a risk of reducing productivity and quality of life. Unhealthy lifestyles and high stress levels are important risk factors commonly found in the productive age group. This study aimed to analyze the relationship between lifestyle and stress levels with the incidence of hypertension in the productive age group at Sariasih Ciputat Hospital. A quantitative cross-sectional correlational study was conducted involving 63 respondents using simple random sampling. Data collection was conducted using a questionnaire. The data obtained were statistically analysed using the chi-square test. Most respondents were middle-aged adults (41–60 years; 44.4%), male (66.7%), and had a basic educational background (52.4%). The majority reported an unhealthy lifestyle (60.3%), moderate stress levels (55.6%), and moderate hypertension (58.7%). Statistical analysis revealed a significant relationship between lifestyle and hypertension (p < 0.001) as well as between stress levels and hypertension (p < 0.001). Lifestyle and stress levels were significantly associated with the incidence of hypertension among productive-age adults. These findings highlight the importance of promoting healthy lifestyle behaviors and stress management interventions to prevent and control hypertension in this population